PENGARUH PENERAPAN ONE DAY MINUTATION TERHADAP KINERJA PANITERA PENGGANTI DI PENGADILAN AGAMA SORONG - Jariyah, Ainun (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2024)
This research aims to analyze the impact of implementing one day minutes on the performance of substitute clerks at the Sorong Religious Court. This system requires the completion of the case file minute process within one working day, with the hope of increasing the efficiency and effectiveness of judicial services. The research method used is descriptive qualitative with data collection through interviews and documentation. The research results show that the implementation of one day minutation significantly increases the work efficiency of Substitute Registrars, increases discipline, and reduces the backlog of case files. This has a positive impact on improving the quality of service to the parties and legal certainty. However, on the other hand, this research also identifies several challenges faced by Substitute Registrars in implementing this system. Such as increasing workload and lack of human resources. This research provides an important contribution to judicial policy makers, especially related to optimizing clerkship performance.